2020
DOI: 10.1186/s12931-020-01581-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS coronavirus 2: from genome to infectome

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) belongs to the group of Betacoronaviruses. The SARS-CoV-2 is closely related to SARS-CoV-1 and probably originated either from bats or pangolins. SARS-CoV-2 is an etiological agent of COVID-19, causing mild to severe respiratory disease which escalates to acute respiratory distress syndrome (ARDS) or multi-organ failure. The virus was first reported from the animal market in Hunan, Hubei province of China in the month of December, 2019, and was rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 153 publications
(212 reference statements)
1
62
0
4
Order By: Relevance
“…SARS-CoV-2 virus has a single stranded RNA genome, whose size ranges from 29.8 kb to 29.9 kb [ 3 ] [ 4 ]. The genomic repertoire of SARS-CoV-2 is as follows; 5’-UTR, replication complex genes (ORF1a and ORF1b) encoding 16 non-structural proteins, structural protein encoding genes like spike (S), envelope (E), membrane (M), and nucleocapsid (N), few accessory protein encoding ORFs (ORF3a, ORF6, ORF7a, ORF7b, ORF8 and ORF9), 3’-UTRs and a Poly Adenine Tail [ 5 ]. Structural proteins facilitate the viral entry to host cells, its assembly and maturation, whereas non-structural proteins are mostly involved in genetic replication and transcription.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 virus has a single stranded RNA genome, whose size ranges from 29.8 kb to 29.9 kb [ 3 ] [ 4 ]. The genomic repertoire of SARS-CoV-2 is as follows; 5’-UTR, replication complex genes (ORF1a and ORF1b) encoding 16 non-structural proteins, structural protein encoding genes like spike (S), envelope (E), membrane (M), and nucleocapsid (N), few accessory protein encoding ORFs (ORF3a, ORF6, ORF7a, ORF7b, ORF8 and ORF9), 3’-UTRs and a Poly Adenine Tail [ 5 ]. Structural proteins facilitate the viral entry to host cells, its assembly and maturation, whereas non-structural proteins are mostly involved in genetic replication and transcription.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 belongs to the beta genus of the Coronaviridae family, a group of single stranded positive sense RNA viruses able to affect humans and animals [10]. The name of Vaccines 2021, 9, 797 2 of 21 this type of viruses comes from the Latin word "corona" that means crown, given due to the appearance of the lipid envelope of the virions, which presents distinctive club-shaped projections [11].…”
Section: Introductionmentioning
confidence: 99%
“…Canonical biogenesis of miRNA is a multi‐step process involving transcription of viral miRNA gene by RNA pol II and formation of a structure called as pri‐miRNA, its breakdown by Drosha endonuclease and DiGeorge syndrome critical region 8 (DGCR8) complex in the form of a hairpin structure called as pre‐miRNA, its extraction from the nucleus and maturation through Dicer endonuclease, eventually joining the RNA‐induced silencing complex (RISC) and suppressing expression of host genes 15 . Cell penetration by SARS‐CoV‐2 is mediated by membrane fusion process, in which a +ssRNA‐sense genome is delivered into the cytoplasm, serving as a template for virus replication process utilizing virally encoded RNA‐dependent RNA polymerase (RdRp), and ultimately, protein synthesis in fact, miRNA biogenesis process in cytoplasmic viruses is performed by non‐canonical miRNA biogenesis pathways in Drosha‐ or Dicer‐independent manner 16,17 . It has recently been shown that one of the main mechanisms of virus pathogenesis is targeting key human genes and suppressing their expression through viral miRNAs 18 .…”
Section: Introductionmentioning
confidence: 99%